Nano antiskid composite material and preparation method thereof

By using nanoscale fillers in ice-surface anti-slip sole materials to compositely modify the thermoplastic elastomer base material, the problem of low fiber wear resistance in existing materials is solved, achieving longer-lasting anti-slip performance and a simplified manufacturing process. .

CN119350792APending Publication Date: 2025-01-24SICHUAN UNIV

Patent Information

Application Number
CN202411512153.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing ice-surface anti-slip sole materials have low wear resistance and are easy to fall off, resulting in a short-lasting anti-slip performance.

Method used

The nano -grade fillers (such as carbon nano fiber or MXENE) compound the thermoplastic elastic body material, and destructive treatment of its surface to form nano -anti -slip composite materials.

Benefits of technology

The wear resistance and anti-skid performance of the material are improved, so that it can still maintain a good anti-skid effect after wear, simplify the manufacturing process, and increase the possibility of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350792A_ABST
    Figure CN119350792A_ABST
Patent Text Reader

Abstract

The invention discloses a nanometer antiskid composite material and a preparation method thereof, and belongs to the technical field of antiskid materials. The nanometer antiskid composite material is prepared from the following raw materials in parts by mass: 90 to 110 parts of styrene-ethylene / butylene-styrene block copolymer, 25 to 35 parts of paraffin oil, 0.3 to 0.4 part of antioxidant 1010, 0.2 to 0.8 part of calcium stearate and 5 to 30 parts of nanometer filler, wherein the nanometer filler is carbon nanofiber or Mxene. A thermoplastic elastomer base material is subjected to compound modification by adopting a nanoscale filler, and the surface of the thermoplastic elastomer base material is subjected to damage treatment, so that the problem that in an existing ice surface anti-slip sole material, micron-sized fibers are lower than the base material in wear resistance and are easy to fall off in the wear process, and further the anti-slip performance is not lasting is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-skid materials, and in particular relates to a nano anti-skid composite material and a preparation method thereof. Background Art

[0002] With the increase of ice and snow weather in winter, people often slip due to icy roads during outdoor activities, especially among the elderly. Slipping may cause serious injuries or even death. Traditional anti-skid soles usually adopt spikes or pattern designs. Although they can provide a certain anti-skid effect, in some cases, such as ordinary hard ground spikes are more likely to slip, and the patterns are stuck on the ice and snow, the anti-skid effect will be greatly reduced. In the prior art, glass fiber and nylon fiber are mainly added to anti-skid composite materials to play the main anti-skid function, but the sizes of both fibers are millimeter or micron level; in the production process of anti-skid composite materials, complex techniques and steps are required to make the fibers vertically arranged on the surface of the substrate, which is difficult to implement in the production of practical application products. Therefore, the development of high-performance, easy-to-scale ice anti-skid materials is crucial to improving the safety and convenience of winter outdoor activities. Summary of the invention

[0003] In response to the above-mentioned prior art, the present invention provides a nano-anti-slip composite material and a preparation method thereof, which uses nano-scale fillers to compositely modify a thermoplastic elastomer substrate and performs a destructive treatment on its surface, thereby solving the problem that the micron-scale fibers in the existing anti-slip sole materials for ice surfaces have lower wear resistance than the substrate and are easy to fall off during wear, which leads to a short-lasting anti-slip performance.

[0004] In order to achieve the above-mentioned object, the technical solution adopted by the present invention is: to provide a nano anti-slip composite material, comprising the following raw materials in parts by weight: 90 to 110 parts of styrene-ethylene / butylene-styrene block copolymer (SEBS), 25 to 35 parts of paraffin oil, 0.3 to 0.4 parts of antioxidant 1010, 0.2 to 0.8 parts of calcium stearate and 5 to 30 parts of nano filler, wherein the nano filler is carbon nanofiber (CNF) or Mxene.

[0005] Based on the above technical solution, the present invention can also be improved as follows.

[0006] Furthermore, the carbon nanofibers have a diameter of 100 nm and a length of 50 to 200 μm.

[0007] Furthermore, the nano anti-slip composite material includes the following raw materials in parts by weight: 100 parts of styrene-ethylene / butylene-styrene block copolymer, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 15 parts of nano filler.

[0008] Furthermore, the nano anti-slip composite material includes the following raw materials in parts by weight: 100 parts of styrene-ethylene / butylene-styrene block copolymer, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 25 parts of nano filler.

[0009] Furthermore, the preparation method of the above-mentioned nano anti-slip composite material comprises the following steps:

[0010] (1) Mixing styrene-ethylene / butylene-styrene block copolymer and paraffin oil at a speed of 55-65 rpm for 5-8 minutes, and then standing for more than 48 hours to obtain oil-filled SEBS;

[0011] (2) Mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate at a temperature of 150 to 170° C., a rotation speed of 50 to 70 rpm, and a time of 10 to 15 min to obtain a mixture A;

[0012] (3) adding nanofiller to mixed material A, and mixing for 10 to 20 minutes at a rotation speed of 50 to 70 rpm to obtain mixed material B;

[0013] (4) hot pressing the mixed material B at a temperature of 160 to 180° C. and a pressure of 0.9 to 1.1 MPa to obtain a sheet material;

[0014] (5) Removing 0.3 to 0.6 mm of the surface layer of the sheet material to obtain a nano-anti-slip composite material

[0015] Furthermore, in step (1), the rotation speed is 60 rpm and the time is 5 min.

[0016] Furthermore, in step (2), the temperature is 160° C., the rotation speed is 60 rpm, and the time is 12 min.

[0017] Furthermore, in step (3), the rotation speed is 60 rpm and the time is 15 min.

[0018] Furthermore, in step (4), the temperature is 170° C. and the pressure is 1 MPa.

[0019] Furthermore, in step (5), 0.5 mm of the surface layer of the sheet material is removed.

[0020] The beneficial effects of the present invention are as follows: SEBS is selected as the base material of the present invention, SEBS does not contain active carbon-carbon double bonds, has excellent tolerance to ozone and ultraviolet rays, and has good outdoor weather resistance; in addition, SEBS can be directly thermoplastically processed and formed, has excellent application properties of rubber without vulcanization, and leftover materials can be recycled without damaging the physical properties and processing properties of the elastomer, and is safe and environmentally friendly. The nano anti-skid composite material prepared by the present invention has the following advantages: (1) in the material preparation process, the traditional fiber alignment step is omitted, the manufacturing process is simplified, a large amount of manpower and material resources are saved, and the possibility of mass production is improved; (2) the nano-scale filler has a smaller diameter, and more fiber protrusions can be formed on the same area, which can increase the surface roughness and generate more contact with the ice surface, thereby improving the traction on the ice surface; (3) the addition of carbon nanofibers changes the SEBS substrate from hydrophilic to highly hydrophobic, and this synergistic effect can further enhance the composite material's ability to maintain good anti-skid performance in a slippery environment; (4) when Mxene is composited with the substrate SEBS, the wettability between the two materials is good, the filler is evenly dispersed, and at the same time, the Mxene nanosheets are partially agglomerated on the SEBS surface to form a hierarchical surface texture, which increases the surface roughness and can still maintain anti-skid performance after wear, so that the nano anti-skid composite material has better mechanical locking (anti-skid) ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the surface contact angle of the nano anti-slip composite material prepared in Example 2. DETAILED DESCRIPTION

[0022] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0023] Example 1

[0024] A nano anti-slip composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 15 parts of nano filler CNF, wherein the diameter of CNF is 100 nm and the length is about 50 nm. The preparation steps of the nano anti-slip composite material are as follows:

[0025] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 60 rpm for 5 min, and then taken out and allowed to stand for 48 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0026] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in a torque rheometer at a temperature of 160° C., a rotation speed of 60 rpm, and a time of 12 min to obtain a mixture A;

[0027] (3) Adding nanofiller to mixture A, mixing at a rotation speed of 60 rpm for 15 min after the torque stabilizes again, to obtain mixture B;

[0028] (4) hot pressing the mixed material B at a temperature of 170° C. and a pressure of 1 MPa to obtain a sheet material with a thickness of about 5 mm;

[0029] (5) Use sandpaper to remove 0.5 mm of the surface layer of the sheet material to expose the nanofiller, thereby obtaining a nano anti-slip composite material.

[0030] Example 2

[0031] A nano anti-slip composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 25 parts of nano filler CNF, wherein the diameter of CNF is 100 nm and the length is about 200 nm. The preparation steps of the nano anti-slip composite material are as follows:

[0032] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 55 rpm for 8 min, and then taken out and allowed to stand for 60 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0033] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in an internal mixer at a temperature of 150° C. and a rotation speed of 70 rpm for 15 min to obtain a mixture A;

[0034] (3) Adding nanofiller to mixed material A, mixing at a speed of 50 rpm for 20 min after the torque stabilizes again, to obtain mixed material B;

[0035] (4) hot pressing the mixed material B at a temperature of 160° C. and a pressure of 1.1 MPa to obtain a sheet material with a thickness of about 5 mm;

[0036] (5) Cut and remove 0.3 mm of the surface layer of the sheet material to expose the nanofiller, thereby obtaining a nano anti-slip composite material.

[0037] Example 3

[0038] A nano anti-skid composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 15 parts of nano filler Mxene; the preparation steps of the nano anti-skid composite material are as follows:

[0039] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 65 rpm for 5 min, and then taken out and allowed to stand for 48 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0040] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in a torque rheometer at a temperature of 170° C., a rotation speed of 50 rpm, and a time of 10 min to obtain a mixture A;

[0041] (3) Adding nanofiller to mixed material A, mixing at a rotation speed of 70 rpm for 10 min after the torque stabilizes again, to obtain mixed material B;

[0042] (4) hot pressing the mixed material B at a temperature of 180° C. and a pressure of 0.9 MPa to obtain a sheet material with a thickness of about 5 mm;

[0043] (5) Use sandpaper to remove 0.6 mm of the surface layer of the sheet material to expose the nanofiller, thereby obtaining a nano anti-slip composite material.

[0044] Example 4

[0045] A nano anti-skid composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 25 parts of nano filler Mxene; the preparation steps of the nano anti-skid composite material are the same as those in Example 1.

[0046] Comparative Example 1

[0047] A composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 15 parts of glass fiber (GF), 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 1 part of silane coupling agent KH-550; wherein the diameter of GF is about 12 μm and the length is about 4 mm; the preparation steps of the composite material are as follows:

[0048] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 60 rpm for 5 min, and then taken out and allowed to stand for 48 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0049] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in a torque rheometer at a temperature of 160° C., a rotation speed of 60 rpm, and a time of 12 min to obtain a mixture A;

[0050] (3) GF and silane coupling agent KH-550 were added to mixed material A, and after the torque became stable again, mixed at a speed of 60 rpm for 15 min to obtain mixed material B;

[0051] (4) hot pressing the mixed material B at a temperature of 170° C. and a pressure of 1 MPa to obtain a sheet material with a thickness of about 5 mm;

[0052] (5) Use sandpaper to remove 0.5 mm of the surface layer of the sheet material to obtain a composite material.

[0053] Comparative Example 2

[0054] A composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010, 0.5 parts of calcium stearate and 25 parts of nanofiller CNF, wherein the diameter of the CNF is 100 nm and the length is about 50 nm. The preparation steps of the composite material are as follows:

[0055] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 60 rpm for 5 min, and then taken out and allowed to stand for 48 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0056] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in a torque rheometer at a temperature of 160° C., a rotation speed of 60 rpm, and a time of 12 min to obtain a mixture A;

[0057] (3) Adding nanofiller to mixture A, mixing at a rotation speed of 60 rpm for 15 min after the torque stabilizes again, to obtain mixture B;

[0058] (4) Mixture B is hot-pressed at a temperature of 170° C. and a pressure of 1 MPa to obtain a sheet material with a thickness of about 5 mm, i.e., a composite material.

[0059] Comparative Example 3

[0060] A composite material comprises the following raw materials in parts by weight: 100 parts of SEBS, 30 parts of paraffin oil, 0.3 parts of antioxidant 1010 and 0.5 parts of calcium stearate; the preparation steps of the composite material are as follows:

[0061] (1) SEBS and paraffin oil were mixed in a high-speed mixer at a speed of 60 rpm for 5 min, and then taken out and allowed to stand for 48 h to allow the paraffin oil to fully swell in the SEBS to obtain oil-filled SEBS;

[0062] (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate in a torque rheometer at a temperature of 160° C., a rotation speed of 60 rpm, and a time of 12 min to obtain a mixture A;

[0063] (3) hot pressing the mixed material A at a temperature of 170° C. and a pressure of 1 MPa to obtain a sheet material with a thickness of about 5 mm;

[0064] (4) Use sandpaper to remove 0.5 mm of the surface layer of the sheet material to obtain a composite material.

[0065] Experimental example

[0066] 1. The contact angle of the nano-anti-slip composite material prepared in Example 2 was tested. The test results are as follows: Figure 1 As shown, the surface contact angle of the material is 125.594°, and the addition of CNF changes the SEBS substrate from hydrophilic to hydrophobic.

[0067] 2. The anti-skid coefficient, tensile strength and hardness of the materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested. The test results are shown in Table 1.

[0068] Table 1 Physical properties of the composite materials prepared in the examples and comparative examples

[0069]

[0070] The anti-skid coefficient of the nano-anti-skid composite materials prepared in Examples 1 to 4 is significantly higher than that of Comparative Examples 1 to 3, indicating that the addition of nano-fillers CNF or Mxene significantly improves the anti-skid performance of the entire material on ice. Among them, the addition of CNF changes the SEBS substrate from hydrophilic to highly hydrophobic; when Mxene is composited with the substrate SEBS, the wettability between the two materials is good, the filler is evenly dispersed, and at the same time, the Mxene nanosheets partially agglomerate on the surface of SEBS to form a hierarchical surface texture, which gives it better mechanical locking (anti-skid) ability.

[0071] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A nano anti-slip composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of styrene-ethylene / butylene-styrene block copolymer, 25-35 parts of paraffin oil, 0.3-0.4 parts of antioxidant 1010, 0.2-0.8 parts of calcium stearate and 5-30 parts of nano filler, wherein the nano filler is carbon nanofiber or Mxene.

2. The nano-anti-slip composite material according to claim 1, characterized in that: The carbon nanofiber has a diameter of 100 nm and a length of 50 to 200 μm.

3. The nano-anti-slip composite material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of styrene-ethylene / butylene-styrene block copolymer, 30 parts of paraffin oil, 10100.3 parts of antioxidant, 0.5 parts of calcium stearate and 15 parts of nano filler.

4. The nano-anti-slip composite material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of styrene-ethylene / butylene-styrene block copolymer, 30 parts of paraffin oil, 10100.3 parts of antioxidant, 0.5 parts of calcium stearate and 25 parts of nano filler.

5. The method for preparing the nano-anti-slip composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Mixing styrene-ethylene / butylene-styrene block copolymer and paraffin oil at a speed of 55-65 rpm for 5-8 minutes, and then standing for more than 48 hours to obtain oil-filled SEBS; (2) mixing the oil-extended SEBS, antioxidant 1010 and calcium stearate at a temperature of 150 to 170° C., a rotation speed of 50 to 70 rpm, and a time of 10 to 15 min to obtain a mixture A; (3) adding nanofiller to the mixed material A, and mixing for 10 to 20 minutes at a rotation speed of 50 to 70 rpm to obtain a mixed material B; (4) hot pressing the mixed material B at a temperature of 160 to 180° C. and a pressure of 0.9 to 1.1 MPa to obtain a sheet material; (5) Removing 0.3 to 0.6 mm of the surface layer of the sheet material to obtain the nano anti-slip composite material.

6. The method for preparing the nano-anti-slip composite material according to claim 5, characterized in that: The rotation speed in step (1) is 60 rpm and the time is 5 min.

7. The method for preparing the nano-anti-slip composite material according to claim 5, characterized in that: In step (2), the temperature is 160° C., the rotation speed is 60 rpm, and the time is 12 min.

8. The method for preparing the nano-anti-slip composite material according to claim 5, characterized in that: The rotation speed in step (3) is 60 rpm and the time is 15 min.

9. The method for preparing the nano-anti-slip composite material according to claim 5, characterized in that: The temperature in step (4) is 170° C. and the pressure is 1 MPa.

10. The method for preparing the nano-anti-slip composite material according to claim 5, characterized in that: In step (5), 0.5 mm of the surface layer of the sheet material is removed.

Citation Information

Patent Citations

  • Polyvinyl alcohol-based fiber material for electromagnetic shielding and preparation method thereof

    CN111636115A

  • Tension sensing fiber, yarn, fabric and preparation method of tension sensing fiber

    CN113201802A

  • Disk brake for vehicle

    JP2004308776A

Cited By

  • Water-based inorganic zinc-rich anticorrosive paint and preparation method thereof

    CN119662060A